Weighting The Fire Protection Systems Technical Requirements to Determine Flats Reliability Against Fire Hazards - Aris Aminulwahyu; I Putu Artama Wiguna; Tri Joko Wahyu Adi (Journal of Infrastructure & Facility Asset Management, 2021)
Flats are multi-story buildings built to serve a region that is divided into functionally structured sections, both in horizontal and vertical directions consist of each unit that can be owned and used separately. Flats are often identified as poorly maintained buildings especially in infrastructure and facilities that support the security, convenience, and safety of occupants and buildings. Fire in flats can be caused by various things including human, natural, and accidental factors. Fire prevention can be performed properly when flats manager and occupants can understand the risks that can trigger fires as well as those that can hinder the rescue process. This study tries to find out the weight of fire protection systems technical requirements to determine flats’ reliability against fire hazards based on the Minister of Public Works Regulation, National Fire Protection Association, and American Society For Testing and Materials. Through the filtering phase analyzed with Relative Importance Index followed by weighting phase analyzed with Pairwise Comparison, the result obtained an order of requirements from the highest to lowest weight are Means of Escape (24,1%), Active Protection Systems (18,9%), Passive Protection Systems (14,5%), Utilities (13,5%), Site Planning (10,1%), Occupancies (9,8%) and Housekeeping (9,1%).